Analisis Kinerja Keuangan Daerah Kabupaten Magelang Tahun 2017-2019 - Hilda Mataris; Kumba Digdowiseiso (Populis : Jurnal Sosial dan Humaniora, 2022)
This study aims to analyze the regional financial performance of Magelang Regency in terms of the Ratio of the Degree of Fiscal Decentralization, the Ratio of PAD Effectiveness, Regional Financial Efficiency and the Harmony of Regional Spending. This research is a quantitative descriptive study on the financial condition of the Government of Magelang Regency during the period 2017-2019. Regional Financial Performance Kab. Magelang seen from the RDDF of 17.25% which is in the criteria of being deficient in increasing its PAD. The degree of effectiveness of PAD is 110.29% with the criteria for being very effective, good and capable in the management of PAD. From the REKD side, it was 655.42% with ineffective criteria, that is, the total regional expenditure figure was greater than the realization of PAD. Harmony in Operational Expenditures is at 39.17%, which is less than half of the total Regional Expenditures or less than 50%. The balance of capital expenditures is 18.45%, which reflects that the amount of regional expenditure allocations for capital expenditures is harmoniously below the 20% figure. District Government Magelang still prioritizes short-term annual Operational Expenditures from its APBD compared to Capital Expenditures for long-term development Penelitian ini bertujuan untuk menganalisis kinerja keuangan daerah Kabupaten Magelang di lihat dari rasio derajat desentralisasi fiskal, rasio efektifitas PAD, efisiensi keuangan daerah dan keserasian belanja daerah. Penelitian ini adalah penelitian deskriptif kuantitif pada keadaan keuangan Pemerintah Kabupaten Magelang selama kurun waktu 2017-2019. Kinerja Keungan Daerah Kab. Magelang dilihat dari RDDF sebesar 17,25% yang masuk kriteria kurang dalam meningkatkan PAD-nya. Pada Derajat Efektivitas PAD adalah sebesar 110,29% dengan kriteria sangat efektif, telah baik dan mampu dalam pengelolaan PAD. Dari sisi REKD adalah sebesar 655,42% dengan kriteria tidak efektif, yakni jumlah angka Belanja Daerah lebih besar dari realisasi PAD. Keserasian Belanja Operasional berada diangka 39,17% berada kurang dari separuhnya dari seluruh Total Belanja Daerah atau kurang dari 50%. Keserasian Belanja Modal adalah sebesar 18,45% yang mencerminkan besarnya alokasi belanja daerah untuk belanja modal masih serasi berada dibawah angka 20%. Pemerintah Kab. Magelang masih memprioritaskan Belanja Operasional jangka pendek tahunan dari APBD nya dibandingkan dengan Belanja Modal untuk pembangunan jangka panjang.